2020
DOI: 10.3802/jgo.2020.31.e74
|View full text |Cite
|
Sign up to set email alerts
|

Fertility-sparing treatment for intramucous, moderately differentiated, endometrioid endometrial cancer: a Gynecologic Cancer Inter-Group (GCIG) study

Abstract: Objective: 'The Endometrial Cancer Conservative Treatment (E.C.Co.). A multicentre archive' is a worldwide project endorsed by the Gynecologic Cancer Inter-Group, aimed at registering conservatively treated endometrial cancer (EC) patients. This paper reports the oncological and reproductive outcomes of intramucous, G2, endometrioid EC patients from this archive. Methods: Twenty-three patients (Stage IA, G2, endometrioid EC) were enrolled between January 2004 and March 2019. Primary and secondary endpoints wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
57
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(60 citation statements)
references
References 35 publications
0
57
2
1
Order By: Relevance
“…And, in the hormonal treatment indications of early endometrial cancer, there was still lack of evidence about whether hormonal treatment can be a safe option for endometrial cancer patients with moderately differentiated tumor grade. A Gynecologic Cancer Inter-Group study observed that CR was achieved in 43.4%, 56.5% and 65.2% of the patients after 6, 9, and 12 months from the initiation of progestin, respectively, achieving 73.9% of an overall CR rate [ 45 ]. Although the sample size is very small (23 patients and all were grade 2) the CR rates seem to be identical with the results from previous studies in patients with grade 1.…”
Section: Uterine Corpusmentioning
confidence: 99%
“…And, in the hormonal treatment indications of early endometrial cancer, there was still lack of evidence about whether hormonal treatment can be a safe option for endometrial cancer patients with moderately differentiated tumor grade. A Gynecologic Cancer Inter-Group study observed that CR was achieved in 43.4%, 56.5% and 65.2% of the patients after 6, 9, and 12 months from the initiation of progestin, respectively, achieving 73.9% of an overall CR rate [ 45 ]. Although the sample size is very small (23 patients and all were grade 2) the CR rates seem to be identical with the results from previous studies in patients with grade 1.…”
Section: Uterine Corpusmentioning
confidence: 99%
“…In this issue of the Journal of Gynecologic Oncology , Falcone and colleagues [ 9 ] report on the oncologic and reproductive outcomes in 23 patients with grade 2 endometrial cancer from multiple centers. Patients were treated with a combination of hysteroscopic resection plus progestin therapy with LNG-IUD, megestrol acetate or norethisterone acetate.…”
mentioning
confidence: 99%
“…Recently, Falcone et al [ 1 ] reported the oncologic and reproductive outcomes of fertility-sparing treatment in women with endometrium-confined, grade 2, endometrioid endometrial cancer using Gynecologic Cancer Inter-Group (GCIG)-endorsed registry. This is the largest series ever reported on the grade 2, endometrial cancer [ 1 ]. The complete response rate (73.9%) and recurrence rate (41.1%) in this report was similar with those obtained in grade 1 endometrial cancer [ 1 ].…”
mentioning
confidence: 99%
“…This is the largest series ever reported on the grade 2, endometrial cancer [ 1 ]. The complete response rate (73.9%) and recurrence rate (41.1%) in this report was similar with those obtained in grade 1 endometrial cancer [ 1 ]. Therefore, it seems that fertility-sparing treatment can be a reasonable treatment option for women with endometrium-confined, grade 2, endometrioid endometrial cancer.…”
mentioning
confidence: 99%
See 1 more Smart Citation